2009
DOI: 10.1152/ajpregu.90757.2008
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in macronutrient regulation measured by proton magnetic resonance spectroscopy of human plasma

Abstract: DP. Individual variation in macronutrient regulation measured by proton magnetic resonance spectroscopy of human plasma. Am J Physiol Regul Integr Comp Physiol 297: R202-R209, 2009. First published May 20, 2009 doi:10.1152/ajpregu.90757.2008.-Proton nuclear magnetic resonance ( 1 H-NMR) spectroscopy of plasma provides a global metabolic profiling method that shows promise for clinical diagnostics. However, cross-sectional studies are complicated by a lack of understanding of intraindividual variation, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
1
45
0
1
Order By: Relevance
“…The metabolome, even in healthy phenotypically similar patients, exhibits a considerable variance across the time. [34][35][36] Furthermore, the samples were taken in the emergency Table 3 Predictive accuracy of clinical variables and biomarkers derived from the metabolomic study for recurrent stroke at the 7-day, 90-day, and 1-year follow-up, and during all follow-up room, without controlling for previous food intake. Nevertheless, the results provided were strengthened by the use of 2 independent cohorts.…”
Section: 18mentioning
confidence: 99%
“…The metabolome, even in healthy phenotypically similar patients, exhibits a considerable variance across the time. [34][35][36] Furthermore, the samples were taken in the emergency Table 3 Predictive accuracy of clinical variables and biomarkers derived from the metabolomic study for recurrent stroke at the 7-day, 90-day, and 1-year follow-up, and during all follow-up room, without controlling for previous food intake. Nevertheless, the results provided were strengthened by the use of 2 independent cohorts.…”
Section: 18mentioning
confidence: 99%
“…[41] In the early 1980s, the introduction of superconducting magnets for NMR experiments allowed substantial improvements in resolution of the resonance peaks of metabolites, as did the introduction of pulse sequences that permitted further discrimination of otherwise overlapping resonance peaks. [42] Using iron-based magnets operating at 90 MHz, the 1 H-NMR spectrum of the bile acid, cholic acid, consisted of strong signals for its C 18 , C 19 and C 21 methyl group protons and weaker signals from the protons epimeric to the C 3 α, C 7 α and C 12 α hydroxyl groups. The remainder of the methane and methylene protons from the steroid ring system and the side chain was grouped together into the 'steroid hump'.…”
Section: Analysis Of the Metabolome Historical Methodsmentioning
confidence: 99%
“…For instance, not controlling for the effect of diet or the time of day of sample collection can lead to excessive variation and/or differences between groups that masquerade as biologically relevant changes in metabolite levels. [19] As noted by Scalbert et al, [20] metabolites arising from gut microbiome and the edible plant metabolome far outnumber metabolites produced by human cells. Rat chow diets are an uncontrolled admixture of soy, wheat and fishmeal.…”
Section: Planning a Metabolomics Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al identified three phases in plasma metabolite profiles that corresponded to morning, afternoon, and night [382]. Furthermore, the inter--individual differences in digestion, nutrient absorption, and metabolism introduced additional variability related to these three phases, in which lipid and amino acid levels were found to vary significantly.…”
Section: Iiic Diurnal Variationmentioning
confidence: 99%